Analysist acceptance of video conference at zoom application using technology acceptance model - Djojo, Brata Wibawa; Hafizh, Wisnu; Gui, Anderes; Muhammad Shabir, Shaharudin; Karmawan, I. Gusti Made; Suryanto, , (Institute of Electrical and Electronics Engineers Inc., 2021)
This study aims to analyze acceptance of video conference at Zoom application for distance learning by observing correlation each variable on the research conducted. Data collection method by using questionnaire in June 2021. Pretest was done using Pearson Product Moment for validity testing and using Cronbach Alpha for reliability testing. All items was valid and all variable was reliable. Respondent in this study included junior and senior high school students, diploma and undergraduate students totaling of 393 respondents spread across DKI Jakarta area. Data was analyzed using SmartPLS for hypotheses testing. This study uses Technology Acceptance Model. The result show perceived ease of use has positive influence to perceived usefulness, perceived ease of use and perceived usefulness have positive influence to attitude toward use, perceived usefulness and attitude toward use have positive influence to intention to use video conference. As conclusion, video conferencing on the Zoom application can be accepted as an alternative in distance learning activities, especially during this covid-19 pandemic.